Seeds of Change: Sketching a Black Feminist Afrofuturism for the New Space Age - Page, Nevandria (Atlantis, 2025)
The rapid advancement of human knowledge and technology has positioned us to realize a new colonialism in outer space. Those with a concern for the future cannot afford to refuse outer space altogether, but must actively devise alternatives to the colonial or capitalistic, imagining a just and peaceful future for humanity beyond the Earth. In this paper, I present Afrofuturism, specifically a Black feminist Afrofuturism, as not merely an aesthetic, but a scholarly methodology capable of disrupting the supposedly inevitable and damned futures awaiting humanity in a colonized outer space. I propose three practices comprising a methodology of Black feminist Afrofuturism. Countermemory involves a willful act of refusing dominant colonial, patriarchal, or white supremacist myths, challenging their hegemony and excavating Black knowledge and experiences from beneath their desolate surface. Interdisciplinarity refuses the practice of knowledge generation in isolation and demands direct collaboration—knowledge created in community—to derive new insights and perspectives from the convergence of disparate practices of countermemory. The third practice, worldbuilding, is a speculative exercise undertaken through the deliberate action of imagining or engaging with new visions of the future through a Black feminist or similar critical lens. These imagined worlds of Black feminist Afrofuturism reveal themselves as the muse for the acts of creation which might influence the trajectory of humanity’s future in outer space, whether in the arts, academic research, public policy, or community organization.